Regulatory Effects of Acupuncture on Emotional Disorders in Patients With Menstrual Migraine Without Aura: A Resting-State fMRI Study - Zhang, Yutong; Wang, Ziwen; Du, Jiarong; Liu, Jixin; Xu, Tao; Wang, Xiao; Sun, Mingsheng; Wen, Yi; Li, Dehua; Liao, Huaqiang; Zhao, Yu; Zhao, Ling (Frontiers in Neuroscience, 2021)
Background: Menstrual migraine without aura (MMoA) refers to a specific type of migraine that is associated with the female ovarian cycle. It is particularly serious and has brought huge life pressure and mental burden to female patients. Acupuncture has been commonly used to prevent migraines and relieve concomitant emotional disorders; however, the physiological mechanism underlying this intervention remains unclear. This study aimed to use rsfMRI to investigate whether acupuncture can modulate brain function and if the potential influence on brain activity correlates with improving emotional symptoms in MMoA patients. Methods: Overall, 44 patients were randomly divided into a true acupuncture group and the sham acupuncture (SA) group. Patients underwent rsfMRI before and after 3-month treatment, the amplitude of ALFF and ReHo in rsfMRI were calculated. SAS, SDS, frequency of migraine attacks, visual analogue scale, and intensity of the migraine were used for evaluate the clinical effect. The clinical changes of variables were also used to further assess the correlation with brain activitiy in MMoA patients. Results: After acupuncture treatment, the emotional symptoms of both groups of patients improved, and the clinical symptoms of migraine were alleviated. The major finding of our study was that patients with MMoA showed lower ALFF value in the left anterior cingulate and the value was positively correlated with the decreases in the SAS and SDS scores. In the SA group, common brain regions responded both in ALFF and regional homogeneity values mainly in the insula, and no significant correlations were observed between brain regions and clinical variables.Conclusions: These results indicated that both two acupuncture treatments were helpful in treating migraine and could improve emotion symptoms. TA had a relatively better effect in reducing the frequency of migraine attack than SA. The two therapies have different modulation effects as TA regulates emotional disorders by modulating the frontal-limbic regions, and SA may modulate pain perception through the placebo effect on insula and by indirectly regulating emotional disorders. These findings provided evidence that acupuncture is a complementary and alternative therapy to relieve clinical symptoms in female patients with migraines and could help enhance clinical diagnosis and treatment.